Pengaruh Film “Ada Apa Dengan Cinta 2” Terhadap Perkembangan Pariwisata Di Kabupaten Magelang - Herlambang, Rizqi Maulana; Adikampana, I Made (JURNAL DESTINASI PARIWISATA, 2019)
Tourism destinations in Indonesia have a variety of interesting tourist attractions and many of these tourist attractions become shooting locations or taking pictures of a film scene. By making a tourism destination and tourist attraction becomes a setting of shooting a film is expected to make tourism developing and films “Ada Apa Dengan Cinta 2” is one of the films that took the place of shooting for the film scene in several tourist attractions in Magelang. the purpose of this research are to know determine the influence of the film “Ada Apa Dengan Cinta 2” product development, market and marketing at the Rumah Do’a Bukit Rhema. This research uses qualitative data collected through observation , interview , documentation , informans are selected using purposive procedures. Data analysis method used qualitative data analysis. The result of the research shows are the occurrence of product, market and marketing developments at Rumah Do’a Bukit Rhema after being shooting and appearing on scene films Ada Apa Dengan cinta 2. The government especially tourism ministry is expected to choosing films as a means of tourism promotion. Keywords: Scene film, Tourism attraction, Ada apa dengan cinta 2, Rumah doa bukit rhema